Vulnerability Analysis of Rectorate Building of UIN Mataram against Earthquakes Based on Microtremor Data - Ilham, Ilham (Universitas Jember, 2023)
Lombok Earthquake in 2018 caused several damages to buildings, including buildings at UIN Mataram. Therefore, it is necessary to carry out mitigation efforts to reduce losses caused by the earthquake. This study aims to analyze the level of vulnerability of the Rectorate Building of UIN Mataram based on microtremor data. Microtremor signal recording was performed using a 3-component Digital Portable Seismograph, type TDL 303S with a Feedback Short Period Seismometer sensor type DS-4A, GPS, and Laptop. The recording time for each measurement point was 40 minutes with a sampling rate of 100 Hz. The natural frequency of the Rectorate Building of UIN Mataram is 4.15 Hz for the N-S component, and 4.05 Hz for the E-W component. The natural frequency of the Rectorate Building is following the SNI (2002) standard. The resonance index value of the Rectorate Building with the surrounding land is in a low category so that the Rectorate Building is classified as safe against earthquakes. The highest building Vulnerability Index is on the 3rd floor of the Rectorate building, especially in the south wing. For disaster mitigation, the 3rd floor can be converted as a room with minimal staff to reduce the possibility of casualties in the event of an earthquake in the future.